The clinical characteristics and outcomes of infantile seizures in the first year of life: a single-center study - Anuar, Muhamad Azamin; Zainal Abidin, Muhammad 'Adil; Tan, Soo Hong; Yeap, Cai Fong; Yahaya, Nor Azni (Elsevier, 2024)
Introduction Epilepsy has a high incidence among infants during their first year of life, yet the prognosis can vary significantly. While considerable research has been conducted on infantile spasms, studies examining infantile-onset epilepsy, excluding infantile spasms, remain limited, particularly concerning the factors influencing outcomes. Therefore, our study aims to elucidate seizure control, developmental outcomes, and prognostic factors in infants with epilepsy during their first year of life, within a single-center study in Malaysia.